1999
DOI: 10.1207/s15327655jchn1602_4
|View full text |Cite
|
Sign up to set email alerts
|

Health Concerns and Risk Behaviors of Rural Adolescents

Abstract: Although much has been written about the health status of adolescents, little is known about adolescents' perception of their own health. The purpose of this article is to describe the health concerns of rural adolescents. Two national studies, the Youth Risk Behavior Survey and the National Longitudinal Study of Adolescent Health (Add Health Project), are used as comparisons. Data from the rural survey represent 624 community adolescents attending 4 rural Pennsylvania schools. The students were in the 9th, 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 11 publications
1
9
0
1
Order By: Relevance
“…Social support has been studied repeatedly and shown to offset the negative effects of anger by encouraging health-promoting behaviors (Ebata & Moos, 1994;Puskar, Tusaie-Mumford, Sereika, & Lamb, 1999b;Speilberger, 1999;Yeaton & Sechrest, 1981). Increasing levels of social support have been positively associated with decreasing depressive tendencies (Heponiemi et al, 2006) and reducing alcohol use in adolescent populations (HamdanMansour, Puskar, & Serieka, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Social support has been studied repeatedly and shown to offset the negative effects of anger by encouraging health-promoting behaviors (Ebata & Moos, 1994;Puskar, Tusaie-Mumford, Sereika, & Lamb, 1999b;Speilberger, 1999;Yeaton & Sechrest, 1981). Increasing levels of social support have been positively associated with decreasing depressive tendencies (Heponiemi et al, 2006) and reducing alcohol use in adolescent populations (HamdanMansour, Puskar, & Serieka, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Psychosocial concerns included stressors and coping methods, anxiety, anger, somatic complaints, depression, health, and risk behaviors (Puskar & Martsolf, 1993; Puskar, Ren, Bernardo, Haley, & Stark, 2008; Puskar, Sereika, & Haller, 2003; Puskar, Tusaie-Mumford, Sereika, & Lamb, 1999a and 1999b). Common stressors identified by students were school (exams, tests, and grades), family (fighting with parents and loss of a family member), and friendship/social concerns (girlfriends, boyfriends, and dating) (Puskar & Martsolf).…”
Section: Introductionmentioning
confidence: 99%
“…Common stressors identified by students were school (exams, tests, and grades), family (fighting with parents and loss of a family member), and friendship/social concerns (girlfriends, boyfriends, and dating) (Puskar & Martsolf). Problems identified in another study included confusion about the future, depression, feeling lonely, trouble at home, suicidal thoughts, lack of a best friend, tobacco and alcohol use, sexual abuse, and general health concerns of both a physiological and psychosocial nature (feeling tired, being overweight, and headaches) (Puskar et al, 1999a). Puskar and colleagues also found that depression, negative life events, anxiety, and drug use were related to anger (Puskar et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that lack of health care access and lack of substance use and abuse health services in rural areas makes the adolescents more vulnerable to several risk behaviors such as alcohol use (Puskar, Tusaie-Mumford, Sereika, & Lamb, 1999;Wagenfeld, Murray, Muhatt, & DeBryn, 1994). Rural America has undergone several social and economic changes in the last few decades.…”
mentioning
confidence: 99%
“…Consequently, people in rural communities have to travel for long distances to get this service. Moreover, rural adolescents are in great challenge due to the lack of health care provision and access, poverty, unemployment and transportation problems (Puskar et al, 1999).…”
mentioning
confidence: 99%